DYNAMICS OF GENERAL PHYSICAL FITNESS OF 15-YEAR-OLD GIRLS CYCLISTS PARTICIPATING IN TRAINING GROUPS - Boratov Odiljon (Research Focus International Scientific Journal, 2023)
In this scientific article, the general physical fitness of 15-year-old female cyclists participating in the training group, what changes at the end of the experiment in the experimental and control groups, It is researched how the quality indicators of speed, strength, agility, flexibility, and endurance are formed.